Towards an Integrative Psychological Science Issues, Approaches and Applications - Tripathi, R.C.; Kar, Bhoomika R.; Pande, Namita (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This edited volume examines the new ways of conceptualizing Psychology as an integrative science to understand human problems at the individual, group, societal, and national levels. It focuses on the need for Psychology to move away from its present reductionist perspective to an integrative psychological science perspective. The volume is organized into three main sections: The first discusses the convergence of qualitative and quantitative methodological approaches in Psychology. The second part highlights the importance of social and personal wellness. The third focuses on studying human behaviour in the context of cultural variations and the impact of cultural context on psychological processes. The book includes contributions from leading scholars in psychology in India whose reference to practical, social and political issues of contemporary interest makes the volume stand out. This book serves as a resource to initiate the dialogue about the need, issues, levels, and integration methods in Psychology, which can be scientifically tested and theoretically explained. The comprehensive and authoritative volume is of interest to researchers and scholars in cognitive psychology, clinical psychology, organizational psychology, social psychology and cross-cultural psychology.
Integration of Methods and Psychological processes -- Integrative Psychological Science in Cultural Context -- Integrative Understanding of Social Issues.
Keywords: Psychology; Personality; Difference (Psychology).; Cognitive psychology; Clinical psychology; Behavioral Sciences and Psychology; Personality and Differential Psychology; Cognitive Psychology; Clinical Psychology